1980
DOI: 10.1042/bj1850723
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the position of the double bond in steroid substrates on the efficiency of the proton-transfer reaction by Pseudomonas testosteroni 3-oxo steroid Δ4–Δ5-isomerase

Abstract: Studies of the proton-transfer reaction by Pseudomonas testosteroni 3-oxo steroid Delta(4)-Delta(5)-isomerase with Delta(5(6))- and Delta(5(10))-steroid substrates demonstrate the importance of the position of the double bond for the efficiency of the isomerization process. Thus 3-oxo-Delta(5(6))-substrates have markedly high k(cat.) values, whereas those of 3-oxo-Delta(5(10))-substrates are very low and their apparent K(m) values approach equilibrium dissociation constants. The first step in the isomerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…Further support for this came from the gc-ms analyses of the cell-free incubation products which revealed that under the conditions of the experiment greater than 50% of the racemic 6 reacted. This result is similar to the partial regiospecific promiscuity that has been observed (29,30) between two carbons in the reprotonation step of A5-3-ketosteroid isomerases (in this case the catalytic group has been shown to be a freely rotating carboxylate of an aspartate residue).…”
Section: Substrate (100 µ )supporting
confidence: 80%
“…Further support for this came from the gc-ms analyses of the cell-free incubation products which revealed that under the conditions of the experiment greater than 50% of the racemic 6 reacted. This result is similar to the partial regiospecific promiscuity that has been observed (29,30) between two carbons in the reprotonation step of A5-3-ketosteroid isomerases (in this case the catalytic group has been shown to be a freely rotating carboxylate of an aspartate residue).…”
Section: Substrate (100 µ )supporting
confidence: 80%
“…This too was confirmed by the gc-ms analyses of the cell-free incubation products, which revealed that under the conditions of the experiment greater than 50% of the racemic 3 reacted. This result is similar to the partial regiospecific promiscuity that has been observed between two carbons in the reprotonation step of A5-3-ketosteroid isomerases [in this case the catalytic group has been shown to be a freely rotation carboxylate of an aspartate residue (10,11)].…”
supporting
confidence: 76%
“…The kinetic data were analyzed by double reciprocal plots, and the Km and FmaJt values were obtained by use of a Wilkinson hyperbolic weighted leastsquares program (Wilkinson, 1961). The differing volumes of methanol used in the above experiments were dictated by a compromise between the inhibition of the enzyme by this solvent (Weintraub et al, 1980;Falcoz-Kelly et al, 1968) and the need to maintain steroid solubility.…”
Section: Methodsmentioning
confidence: 99%